2020
DOI: 10.1111/zsc.12454
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Veneridae (Bivalvia) based on mitochondrial genomes

Abstract: Veneridae is one of the most diverse families of bivalve molluscs. However, their phylogenetic relationships among subfamilies have been debated for years. To explore phylogenetic relationships of Veneridae, we sequenced 13 complete mitochondrial genome sequences from eight subfamilies and compared with available complete mitochondrial genome of other Veneridae taxa (18 previously reported sequences). Phylogenetic analyses using probabilistic methods recovered two highly supported clades. In addition, the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
4
10
0
1
Order By: Relevance
“…This finding agreed with Salvi and Mariottini (2012) [5]. The mitochondrial genome analysis showed that P. undulata was clustered with other Tapetinae species [3,6]. Just four partial ITS sequences of P. undulata were deposited in the GenBank database (JN996788, JN996787, JN996750 and EU183531), and the identity of ITS1 and ITS2 of them were just 36.16% and 58.25%, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding agreed with Salvi and Mariottini (2012) [5]. The mitochondrial genome analysis showed that P. undulata was clustered with other Tapetinae species [3,6]. Just four partial ITS sequences of P. undulata were deposited in the GenBank database (JN996788, JN996787, JN996750 and EU183531), and the identity of ITS1 and ITS2 of them were just 36.16% and 58.25%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Many Veneridae species are economically important due to their huge abundance in benthic environments, such as the Manila clam Ruditapes philippinarum, the northern quahog Mercenaria mercenaria, the western Pacific hard clam Meretrix petechialis, the equilateral clam Gomphina aequilatera and the Taca clam Protothaca theca [1][2][3]. The classification system and phylogenetic re-lationships of Veneridae have been based mainly on morphological characteristics and molecular data (mitochondrial and nuclear sequences) [1,2,[4][5][6], which are currently un-der debate. Problems with existing classification methods are attributed to (1) the con-vergence of the evolutionary and phenotypic plasticity of morphological traits in most venerids [6]; (2) double uniparental inheritance (DUI) of mitochondrial DNA in some Veneridae species [7][8][9];…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be used to investigate the ancestral lineage of phylogeny, and to establish the mechanism of gene replication, regulation and rearrangement. Bivalves of molluscs have highly variable mitochondrial gene sequences, and are the most mutated species in metazoa [ 61 , 62 ]. In the study, we selected some species from four orders of the superorder Impardentia, Venerida, Cardiida, Adapedonta and Lucinida as representatives of bivalves to study mitochondrial gene rearrangement ( Fig 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) exhibits special characteristics that differ from the nuclear genome, such as rapid evolution, maternal inheritance, and lack of recombination [1], and has been an e cient tool and widely used in molluscan evolutionary and phylogenetic analyses [2,3]. Molluscan mtDNA is nearly a closed circular molecule, always containing 13 protein-coding genes (NADH dehydrogenase subunits 1-6 and 4L, ATPase subunits six and eight, cytochrome oxidase subunits 1-3, and cytochrome b), 22 transfer RNA genes and two ribosomal RNAs (rrnS and rrnL) [4,5], with missing ATPase subunits eight, variable tRNAs and extra rrnS in some species [6][7][8]. Different mtDNA composition would result in functional diversity, as mtDNA carries genetic information essential to mitochondrial function [9], thus it's interesting to explore the difference of mtDNA related to adaptive evolution.…”
Section: Introductionmentioning
confidence: 99%